Pelatihan E-Commerce Untuk Meningkatkan Pendapatan Melalui Kokedama (Pelatihan Daring) Bagi Kumpulan Marga Rajagukguk Se-Kisaran Kabupaten Asahan - Jeperson Hutahaean; Neni Mulyani; Zulfi Azhar (Forum Kerjasama Pendidikan Tinggi, 2020)
The community service team of STMIK Royal conducted training with the Margarajagukguk Group throughout the Asahan District in carrying out community service activities at the institution using online. This community service activity team provides training to participants on E-Commerce training to increase income through Kokedama (Online Training) for the Rajagukguk Clan Group in Kisaran, Asahan Regency. Training in the use of IT, especially e-commerce in expanding market share, is needed for the Rajagukguk Kisaran clan group in particular, who are able to compete in today's global business. By utilizing e-commerce promotions and sales can be carried out throughout the world without time constraints and at a very low cost than conventional promotions